The role of insurance companies on enhancing financial inclusion in Algeria- case study of cash insurance during the period (2012-2019) - Daradji, anis; metarref, Awatef (Journal of Research in Finance and Accounting, 2026)
This study aims to measure the extent to which insurance companies contribute to enhancing financial inclusion in Algeria, by addressing the situation of the insurance company (CASH) during the period (2012-2019), we relied in our study on the descriptive and analytical approach to describe the problem and analysis of the associated data, and we also relied on the statistical approach to modeling the relationship between the insurance sector and financial inclusion, and we have found a significant relationship between the variables of the study, but the contribution of the insurance sector to the promotion of financial inclusion in the financial coverage sector Algeria is weak, and this is due to several factors, Some are directly related to insurance activity and others are for external reasons that insurance companies cannot control.